When Do the Rich Vote Less Than the Poor and Why? Explaining Turnout Inequality across the World. Issue 3 (11th September 2014) - Kasara, Kimuli; Suryanarayan, Pavithra
Abstract : The conventional wisdom that the poor are less likely to vote than the rich is based upon research on voting behavior in advanced industrialized countries. However, in some places, the relationship between turnout and socioeconomic status is reversed. We argue that the potential tax exposure of the rich explains the positive relationship between income and voting in some places and not others. Where the rich anticipate taxation, they have a greater incentive to participate in politics, and politicians are more likely to use fiscal policy to gain support. We explore two factors affecting the tax exposure of the rich—the political salience of redistribution in party politics and the state's extractive capacity. Using survey data from developed and developing countries, we demonstrate that the rich turn out to vote at higher rates when the political preferences of the rich and poor diverge and where bureaucratic capacity is high.